Initial characterization of the SAFIR prototype PET-MR scanner - Ritzer, Christian Edwin; Becker, Robert; Buck, Alfred; Commichau, Volker; Debus, Jan; Djambazov, Lubomir; Eleftheriou, Afroditi; Fischer, Jannis Nikolaus Rudolf; Fischer, Peter; Ito, Mikiko; Khateri, Parisa; Lustermann, Werner; et al. (IEEE transactions on radiation and plasma medical sciences, 2020)
The SAFIR collaboration is currently developing a high-rate positron emission tomography (PET) insert to study fast kinetic processes in small animals. Our insert is designed for simultaneous image acquisition with a preclinical 7 T magnetic resonance (MR) imaging device. In contrast to existing preclinical PET scanners and inserts, our hardware is optimized for high-rate measurements with source activities up to 500 MBq. As a first step, the SAFIR Prototype insert was constructed. This already incorporates the final components, but has a reduced axial field-of-view (35.6 mm). We use lutetiumyttrium oxyorthosilicate crystals (2.12 mm × 2.12 mm × 13 mm) one-to-one coupled to silicon photomultipliers. All analog signals are digitized within the insert. We use 49 MR-compatible dc- dc converters in the insert to provide the power to all readout electronics. After shimming, no degradation of the homogeneity of the static B0 field in the MR scanner was observed. During full operation, we saw a minor reduction in the signal-to-noise ratio of the MR data of 4.9%. With a low activity point source (22Na 0.65 MBq) we obtained a coincidence energy resolution of 13.8% full width at half maximum (FWhM) and a coincidence timing resolution of 194 ps (FWhM). First PET/MR rat brain and high-rate mouse cardiac images (84.9 MBq) are shown in this article.
Gesehen am 02.01.2026